SPACE CONTROL CONCEPT : A COMPARISON BETWEEN SPACE LEGAL THEORY AND INDONESIAN LAW - Pranadita, Nugraha; Rosidawati, Imas; Rahmatullah, Tansah (Media Hukum, 2019)
The purpose of the study is to provide a theoretical basis on the discussion of space by comparing the theory of space law with Indonesian laws related to space. Nowadays, space is no longer empty land, no man's land, but has become an arena of competition for the interests of various countries and international organizations. As space currently has limitless economic and strategic values. To utilize space optimally, an understanding between the parties concerned is necessary. Thus, the existence of the theory of space law becomes a vital issue in bridging the gap between the needs and availability of area in space as not every position in space has the same economic and strategic value. The research was conducted by using the method of doctrinal legal research using the conceptual and legal approach which is explained descriptively by analysis using the deductive method. The results of the study are going to determine the differences in the concept of mastery of space according to the theory of space law and according to Indonesian law.